How Current Chatbots Applications Impact Education: An Overview - Yataco-Irrazábal, Saroff (2023)
The implementation of chatbots in multiple platforms with which man interacts has allowed automating processes and being able to respond to requests, one of its applications is the educational field, where they are still experimenting with good results in some areas and in others analyzing their feasibility, the deployment of this technology has been used both in basic education and in higher education, the former mainly addresses the resolution of simple queries facilitating the work of the teacher, and the latter seeks to go further by offering itself as a learning assistant. This work focuses on understanding the impact that chatbots have on education and their integration in some areas of the educational process, analyzing the results offered by other research and real applications. Chatbots have proved to be effective and increase user efficiency by providing information and being a support, evaluation, and follow-up tool. They have even shown favorable results in several learning levels, being a source that centralizes information without the need for the user to access multiple sources to learn a subject or to monitor the level of learning of students or their own.